La seguridad y prevención de accidentes mayores en la fabricación de explosivos y accesorios en la empresa Explocen C.A. Elaboración de un manual de seguridad interna para los trabajadores. - Cárdenas Pila, Fernando Patricio (2015)
The problem is framed specifically in occupational Safety, which is being handled in daily activities and their impact as such, the increased risk of accidents older with in the manufacturing processes of explosives and accessories. The Company EXPLOCEN C. A. by economic activity has a lot of inputs classified as dangerous, combined with the exposure time is a latent risk in the processes, so it requires so urgent need for occupational risk assessment thus enabling us to identify the risk factors. This research has as main objective to develop and establish appropriate procedures to prevent accidents older in the Company EXPLOCEN C. A., admitting the reduction or minimization of occupational hazards in the manufacturing processes of explosives and accessories. This system of risk prevention is aimed at mitigating the effects of damage caused by an accident older both people, property or the environment, thus preparing the necessary measures to minimize the problems that affect productivity, Physical Security and Integrity Workers. For this research work has been used and research literature review field and which is supported in respect to technical and application words surveys thereby enabling to solve the problems encountered. Matrix Occupational Hazard Evaluation which reflects the predominant risk is that of explosion and fire; the survey concludes that workers need a Handbook Internal Security outlining the safety standards and procedures in the manufacture of explosives and accessories are applied as a source and permanent information.